Phonology and orthography in deaf readers: Evidence from a lateralized ambiguity resolution paradigm. Issue 6 (1st November 2020) - Assor, Haim; Miller, Paul; Peleg, Orna; Eviatar, Zohar
ABSTRACT: This study explored differences between the two hemispheres in processing written words among deaf readers. The main hypothesis was that impoverished phonological abilities of deaf readers may lead to atypical patterns of hemispheric involvement. To test this, deaf participants completed a metalinguistic awareness test to evaluate their orthographic and phonological awareness. Additionally, they were asked to read biased or neutral target sentences ending with an ambiguous homograph, with each sentence followed by the request to make a rapid lexical decision on a target word presented either to the left (LH) or right hemisphere (RH). Targets were either related to the more frequent, dominant, meaning of the homograph, to the less frequent, subordinate, meaning of the homograph or were not related at all. An Inverse Efficiency Score based on both response latency and accuracy was calculated and revealed that deaf readers' RH perform better than their LH. In contrast to hearing readers who in previous studies manifested left hemisphere dominance when completed the same research design. The apparent divergence of deaf readers' hemisphere lateralization from that of hearing counterparts seems to validate previous findings suggesting greater reliance on RH involvement among deaf individuals during visual word recognition.